Cardiometabolic index is associated with increased bone mineral density: a population-based cross-sectional study - Wu, Xujin; Jin, Xixin; Xu, Wei; She, Chang; Li, Liubing; Mao, Yongtao (Frontiers in Public Health, 2024)
Background Osteoporosis is a multifactorial bone disease in which lipid metabolism plays an important role. Bone Mineral Density (BMD) measured by Dual-energy X-ray Absorptiometry (DXA) is a critical indicator for diagnosing osteoporosis. The cardiometabolic index (CMI) is a novel metric that combines two quantitative indicators of blood lipids—triglycerides (TG) and high-density lipoprotein cholesterol (HDL-C). This study explores the association between CMI and BMD and seeks to elucidate the role of lipid metabolism in the context of bone health. Methods Based on the data of the National Health and Nutrition Examination Survey (NHANES) 2017–March 2020-pre-pandemic, weighted multiple linear regression and smooth curve fitting were used to study the relationship between CMI and femoral BMD. Stratified analyses were also conducted for age, gender, BMI, ethnicity, diabetes and hypertension status. And, the saturation threshold effect of CMI was further analyzed using a two-stage linear regression model. Result This study enrolled a total of 1,650 participants (48.7% males), with an average age of 63.0 ± 8.6 years. After adjusting for multiple confounding factors, CMI was positively correlated with total femur BMD, trochanter BMD, and intertrochanter BMD, while the correlation with femur neck BMD was not statistically significant. In the fully adjusted model, each unit increase in CMI was associated with a 0.026 (g/cm2) increase in total femur BMD, a 0.022 (g/cm2) increase in trochanter BMD, and a 0.034 (g/cm2) increase in intertrochanter BMD. Subjects in the highest quartile of CMI had a 0.034 (g/cm2) increase in total femur BMD, a 0.035 (g/cm2) increase in trochanter BMD, and a 0.039 (g/cm2) increase in intertrochanter BMD in the fully-adjusted model compared to those in the lowest quartile. In addition, saturation was observed between CMI and total femur BMD, trochanter BMD and intertrochanter BMD, with saturation thresholds of 1.073, 1.431 and 1.073, respectively. Conclusion CMI is strongly associated with BMD, indicating its potential relevance in bone metabolism. However, the role of CMI in the context of bone health, especially regarding osteoporosis risk, requires further investigation in large-scale prospective studies.